2020
DOI: 10.1177/2333794x20968715
|View full text |Cite
|
Sign up to set email alerts
|

Which Factors Predict Hospital Length-of-Stay for Children Admitted to the Neonatal Intensive Care Unit and Pediatric Ward? A Hospital-Based Prospective Study

Abstract: Background. The ability to accurately predict hospital length of stay (LOS) or time to discharge could aid in resource planning, stimulate quality improvement activities, and provide evidence for future research and medical practice. This study aimed to determine the predictive factors of time to discharge among patients admitted to the neonatal intensive care unit (NICU) and pediatric ward in Goba referral hospital, Ethiopia. Methods. A facility-based prospective follow up study was conducted for 8 months amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
2
15
0
2
Order By: Relevance
“…Similar to other studies, the current study showed that lower birth weight is associated with longer hospital stay. 29 , 30 This is shown by the logistic regression analysis where an increase in birth weight was found to be protective and thus is associated with a shorter hospital stay, ie ≤7 days (AOR = 0.3). Neonates with comorbid illness and neurologic features were more likely to stay longer (AOR = 3.9 and AOR = 4.37 respectively).…”
Section: Discussionmentioning
confidence: 91%
“…Similar to other studies, the current study showed that lower birth weight is associated with longer hospital stay. 29 , 30 This is shown by the logistic regression analysis where an increase in birth weight was found to be protective and thus is associated with a shorter hospital stay, ie ≤7 days (AOR = 0.3). Neonates with comorbid illness and neurologic features were more likely to stay longer (AOR = 3.9 and AOR = 4.37 respectively).…”
Section: Discussionmentioning
confidence: 91%
“…Some differences in the hospital unit's colonization profile can be related to patient's turnover and hospital stay in each unit, as well as the severity illness of inpatients. As seen in the HAI risk factor analysis, longer hospital stay is correlated with the presence of HAI in the current hospitalization, specific HAIrB increase and invasive device use, with several large studies also documenting these correlations (Jia et al, 2019;Sahiledengle et al, 2020;Su et al, 2020). EMG with high patient's turnover (shorter hospital stay), showed less HAIrB load compared to the total bacteria, as well as lower positivity of BL genes, MDR and CARB-R bacteria.…”
Section: Discussionmentioning
confidence: 82%
“…The lower the gestational age the longer the mechanical ventilation, oxygen therapy, and hospital stay. 11 The patients <28 weeks GA are divided into two subgroups: the non-BPD group (n = 19) and the moderate-severe BPD group (n = 27). The main LUS pattern and predictors of BPD at 36 weeks' PMA are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The duration of mechanical ventilation and oxygen therapy determine the severity and degree of BPD. The lower the gestational age the longer the mechanical ventilation, oxygen therapy, and hospital stay 11 …”
Section: Resultsmentioning
confidence: 99%